The role of geographical proximity in innovation: Do regional and local levels really matter? - Natalia Irena Gust-Bardon (Fraunhofer Institute for Systems and Innovation Research ISI, 2012)
Globalisation and the advent of information and communication technology (ICT) change the role of spatial distance in innovation activities. Geographical proximity used to be seen as a necessary condition to share tacit knowledge and to enhance trust between innovators; now this approach is being challenged by claiming that the role played by spatial distance diminishes with time. The aim of this paper is to present territorial innovation models as examples of theories based on assumptions of a crucial role of local environment and spatial distance in innovation processes and to present arguments against the said assumption. The paper concludes advocating the encouragement to cooperate both within the local network area and with distant partners and the creation of territorial innovation models as open systems engaged in interactive learning by global connectivity.
urn:nbn:de:0011-n-2139400
Keywords: 330; Innovation; Distance; Globalization; Business network; Learning process; Regional cluster; Innovation; Entfernung; Globalisierung; Unternehmensnetzwerk; Lernprozess; Regionales Cluster